First Order Nonhomogeneous Linear Differential Polynomials - Belaidi, Benharrat (Miskolc Mathematical Notes, 2010)
In this paper, we investigate the complex oscillation of the nonhomogeneous linear differential polynomial gf D d1f 0 C d0f C b. Here d0./; d1./, b./are meromorphic functions such that at least one of d0./and d1./does not vanish identically with p dj< 1. j D 0; 1/; p. b/< 1, and f is a solution of the differential equation f 00 CA./f D 0; where A./is a transcendental meromorphic function with finite iterated order p. A/D> 0.
Keywords: differential polynomials; linear differential equations; iterated order; iterated expo-nent of convergence of the sequence of distinct zeros; iterated exponent of convergence of thesequence of distinct fixed points